A Review Study on the Traditional Machining of Composite Materials - Ali, Hussein M. (Journal of Research Updates in Polymer Science, 2017)
Composite materials are widely used materials in many industrial applications due to their superior properties. Machining of composite materials is difficult to carry out due to the anisotropic and non-homogeneous structures of composites and are mostly prepared in laminate form before undergoing the machining process. Machining of these materials is inevitable although they are manufactured to near net shape. This becomes more important when new product designs and shapes poses tougher dimensional and performance constraints like surface finish, dimensional tolerances & material removal rate etc. Thus many researchers in the past have attempted to study the machining of composite materials to know the effect of various process parameters upon the quality of machining characteristics. In this paper an overview of the various issues involved in the machining of the main types of composite materials is presented. Literature review reveals that current research focuses on the traditional machining of glass and carbon fiber reinforced plastics to reduce or eliminate the problem of delamination and dimensional accuracy.